Exploring Pharmacological Mechanisms, Clinical Trials and Patent Landscapes of Berberine: A Review - Saini, Vishakha; Deswal, Geeta; Dhingra, Ashwani K.; Singh, Jagdeep; Kumar, Jatin; Saini, Avdesh (Natural Products Journal, The, 2026)
Traditional Chinese medicine has used berberine (BBR) for a long time. Berberine is a natural compound found in several plants, including Berberis lyceum Royle, Berberis thunbergii DC, Berberis koreana Palib., Berberis vulgaris L., Mahonia aquifolium, Mahonia bealei (Fort.) Carr., and Chelidonium majus L. Berberine is believed to help treat many diseases, such as ovarian and colorectal cancer, high blood pressure, Parkinson's and Alzheimer's disease, diabetes, heart disorders, depression, viral infections, and inflammatory diseases. However, when taken orally, berberine quickly breaks down in the body, leading to low levels in the bloodstream. This means that its absorption in the intestines is limited, which reduces its effectiveness despite its potential health benefits. The liver is the main organ that processes and uses berberine in both animals and humans, and about 84% of berberine and its byproducts are excreted in the feces. We thoroughly reviewed the available research on berberine from reliable sources like PubMed, ScienceDirect, ClinicalTrials.gov, and Scopus. Our study summarizes the latest findings on the therapeutic benefits of berberine and provides updated information on clinical research and patents. This review covers the various pharmacological effects of berberine, including its use in treating Alzheimer's disease, high blood pressure, neuroprotective effects, anti-arrhythmia, Parkinson's disease, diabetes, cancer, and depression.
Keywords: neuro-effectiveness activity